The history of legal theories in e-contract - Mohd Shariff, Roos Niza (2014)
This paper is the study of how individuals and businesses develop and construct legal agreements through electronic means.E-contract works faster in order to promote certain outcomes, but can also contain a level of legal and moral hiatus stemming from the nature of the contract and the distance of the parties.This paper describes the history of legal theories apply to the formation phase of e-contract, and not contract per se. It begins with e-contracting and follows with legal theories that recognize legal enforce ability.It then discusses essential legal requirements for e-contract formation resulted from these legal theories.